2012
DOI: 10.4103/0970-0358.105960
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of traumatic brachial plexus injury patients treated at an Indian centre

Abstract: Background:Epidemiological studies on traumatic brachial plexus injuries are few and these studies help us to improve the treatment, rehabilitation of these patients and to allocate the resources required in their management. Epidemiological factors can vary in different countries. We wanted to know the situation in an Indian centre.Materials and Methods:Data regarding age, sex, affected side, mode of injury, distribution of paralysis, associated injuries, pain at the time of presentation and the index procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
64
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 18 publications
2
64
1
1
Order By: Relevance
“…Quality of life was associated with pain in items related to pain and functional capacity domains. The characteristics of sex, age, type of accident and extent of injury were similar to other studies evaluating individuals with TBPI 6,7,8,10,17 . The majority of our patients had completed high school, but they were unemployed.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…Quality of life was associated with pain in items related to pain and functional capacity domains. The characteristics of sex, age, type of accident and extent of injury were similar to other studies evaluating individuals with TBPI 6,7,8,10,17 . The majority of our patients had completed high school, but they were unemployed.…”
Section: Discussionsupporting
confidence: 65%
“…The prevalence of pain in these TBPI injuries is usually elevated 5,6,8,9,10 . Only one study found conflicting results 7 . As in our results, the pain usually begins suddenly and is located in the hand 1,11,19 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations